2005
DOI: 10.2117/psysoc.2005.120
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Fixation Related Potential to Stimuli Simulating the Vision of an Older Adult

Abstract: The eye-fixation related potential (EFRP) is a type of visual evoked potential (VEP). In the present study, the effects of simulating the vision of an older adult (Nakano, Higuchi, & Yamamoto, 1996) on the EFRP of young adults were investigated. The EFRP was measured under three conditions: the N condition (original stimulus without any image processing), the CS condition (simulation of a 70-year old person's contrast sensitivity and spectral transmittance), and the C condition (simulation of a 70-year old per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…7). Note that the finding of dominant occipital sources during visual search agrees with past event-related potential work that has associated the saccadic -response during conditions of visual search (or conditions resembling visual search) with an occipital source (Kazai et al 2005;Kurtzberg et al 1979;Takeda et al 2001).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…7). Note that the finding of dominant occipital sources during visual search agrees with past event-related potential work that has associated the saccadic -response during conditions of visual search (or conditions resembling visual search) with an occipital source (Kazai et al 2005;Kurtzberg et al 1979;Takeda et al 2001).…”
Section: Discussionsupporting
confidence: 87%
“…The GLM-based approach was therefore applied here to test the hypothesis that different sizes of eye movements are associated with different neural activity during visual search. In agreement with past event-related studies (Kazai et al 2005;Kurtzberg et al 1979;Takeda et al 2001), it was found by applying the GLM approach that the saccade onset-triggered neural responses that were observed during a visual search task had a dominant occipital component.…”
supporting
confidence: 89%